Targeting myelin lipid metabolism as a potential therapeutic strategy in a model of CMT1A neuropathy - Fledrich, Robert; Abdelaal, T.; Rasch, L.; Bansal, V.; Schütza, V.; Brügger, Britta; Lüchtenborg, Christian; Prukop, T.; Stenzel, J.; Rahman, R. U.; Hermes, D.; Ewers, D.; et al. (Nature Communications, 2018)
Charcot-Marie-Tooth disease 1A (CMT1A) is a peripheral demyelinating disease. Here, the authors demonstrate in a rodent model of CMT1A that Schwann cells have impairments in lipid biosynthesis, and that restoring lipids via diet can reverse the dysmyelinating phenotype in these animals.
Gesehen am 22.04.2020